Teaching Exchange: Medical Students’ Experience with a Pre-recorded Seminar on Multimorbidity During Coronavirus Disease 2019 Pandemic - Prazeres, Filipe (Cerrahpaşa Medical Journal, 2023)
Objective: The aim of this report is to describe lessons learned with a distance learning activity in substitution for in-class study on the management of multimorbidity. Methods: A total of 140 fifth-year medical students received a pre-recorded slide show with narration and were asked to return by e-mail 3 take-home messages of what they had learned about multimorbidity. Students’ learning is presented by means of a mind map. Results: Correct take-home messages were returned in 95.2% of the cases. This distance learning activity increased students’ knowledge regarding the topic multimorbidity. Conclusion: A pre-recorded slide show with the narration was a valid substitute for the in-class multimorbidity seminar in a context where person-to- person contact was prohibited in the first wave of the coronavirus disease 2019 pandemic. Cite this article as: Prazeres F. Teaching exchange: Medical students’ experience with a pre-recorded seminar on multimorbidity during coronavirus disease 2019 pandemic. Cerrahpaşa Med J. 2023;47(2):202-205.